2022
DOI: 10.1186/s12348-022-00319-w
|View full text |Cite
|
Sign up to set email alerts
|

Ocular symptoms in COVID-19 infection: a survey study

Abstract: Background Coronavirus disease 2019 (COVID-19) systemic symptoms and sequelae have been studied extensively, but less is known about the characterization, duration, and long-term sequelae of ocular symptoms associated with COVID-19 infection. The purpose of this study was to analyze the frequency, spectrum, and duration of ocular symptoms in participants with COVID-19 infection treated in inpatient and outpatient settings. Methods A retrospective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Previous studies have suggested ocular pain is a common symptom after SARS-CoV-2 infection. [ 14 , 29 , 30 ] We found that the prevalence of ocular pain (9.8%) during SARS-CoV-2 infection was significantly higher than pre-infection (2.3%). Our study was in agreement with Pardhan et al [ 31 ] Ocular pain during the infection period was found to be related to conjunctival hyperemia.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Previous studies have suggested ocular pain is a common symptom after SARS-CoV-2 infection. [ 14 , 29 , 30 ] We found that the prevalence of ocular pain (9.8%) during SARS-CoV-2 infection was significantly higher than pre-infection (2.3%). Our study was in agreement with Pardhan et al [ 31 ] Ocular pain during the infection period was found to be related to conjunctival hyperemia.…”
Section: Discussionmentioning
confidence: 82%
“…The self-reported red eye symptom among SARS-CoV-2 infection was 6.4%, and conjunctival hyperemia diagnosed by split lamp examination was 9.1% when recovery In previous studies, the rate of conjunctival hyperemia related to SARS-CoV-2 infection was 0.8% to 31%. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, the diagnosis of conjunctival hyperemia in other studies was based on phone call interviews [8][9][10][11][12][13][14][15] or by examination with a flashlight or portable slit lamp. [16][17][18][19][20][21] In our study, the diagnosis of conjunctival hyperemia consisted of face-to-face interviewing and examination using a slit lamp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that main post COVID-19 infection patient's complaint was pain, red eye, diminution of vision and itching in percentage of (37.5%,28.6%,18.2% and 14.3%) respectively. While McHarg et al [13] reported that most common post COVID-19 patient's complaint were itching, red eye, pain and blurred vision in percentage of (24.9%, 24.5%,24.5% and 22.7%) respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The secretion is serous, often scarce, but never purulent unless bacterial co-infection occurs, with abundant colorable mononuclear cells in the smear. There, electron microscopy (EM) and immunoelectron microscopy (IEM) allow the identification and characterization of viral particles [ 17 ], while PCR is superior to ELISA for sensitivity and accuracy in detecting infections [ 18 ], where the conjunctiva and cornea seem to be the ophthalmic structures most affected by viral infections, as previously summarized by Frezzotti and Guerra [ 19 ], Sen et al [ 20 ], and McHang et al [ 21 ]. A new discovery showed for the first time that in the tears of vaccinated COVID-19 patients, ocular secretory IgA (sIgA) values are remarkably different vs. those of non-vaccinated patients [ 22 ], with significant differences in available vaccines.…”
Section: Opinionmentioning
confidence: 99%